2013
DOI: 10.1080/00405000.2013.809186
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thermal properties of multilayered fabrics by full factorial and Taguchi method

Abstract: The present paper reports the thermal and evaporative resistances of multilayered fabric ensembles meant for cold weather conditions. A three-layered structure was used to simulate the multilayered fabric ensemble. Knitted, through air-bonded nonwoven and coated fabrics were used as inner, middle and outer layer fabrics, respectively. Inner and middle layer fabrics were varied in mass per unit area in three different levels. Three different coated fabrics, namely, polyester polymer-coated fabric and two differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Therefore, both selection of materials and layer manipulation with or without air spaces should be considered for the design of cold weather clothing. 37 Same fabrics as those in Table 1 3 R et Significant effects of mass per unit area of the middle layer and the pore size of the outer layer on R et Shabaridharan and Das 35 Same fabrics as those in Table 1 3 R et Significant effects of punch density, thickness, linear density, mass per unit area on R et Wakatsuki et al 38 Meta-aramid and para-aramid 3 THL Significant effect of lamination on THL Williamson et al 39 Linen plies of viscose battings with an inner layer and an outer layer of thin nylon fabrics showed that the inner fibrous battings with a higher fiber content, finer fibers, greater fiber emissivity, higher air permeability, a lower disperse coefficient of surface free water, and a lower moisture absorption rate led to less condensation and moisture absorption. In addition, the permeable outer covering fabrics exhibited advantage for reducing water condensation within the battings.…”
Section: Huangmentioning
confidence: 97%
See 3 more Smart Citations
“…Therefore, both selection of materials and layer manipulation with or without air spaces should be considered for the design of cold weather clothing. 37 Same fabrics as those in Table 1 3 R et Significant effects of mass per unit area of the middle layer and the pore size of the outer layer on R et Shabaridharan and Das 35 Same fabrics as those in Table 1 3 R et Significant effects of punch density, thickness, linear density, mass per unit area on R et Wakatsuki et al 38 Meta-aramid and para-aramid 3 THL Significant effect of lamination on THL Williamson et al 39 Linen plies of viscose battings with an inner layer and an outer layer of thin nylon fabrics showed that the inner fibrous battings with a higher fiber content, finer fibers, greater fiber emissivity, higher air permeability, a lower disperse coefficient of surface free water, and a lower moisture absorption rate led to less condensation and moisture absorption. In addition, the permeable outer covering fabrics exhibited advantage for reducing water condensation within the battings.…”
Section: Huangmentioning
confidence: 97%
“…In addition, the type of coated fabric had a significant effect on the moisture permeability index of multilayer fabric assemblies and the moisture permeability index of the polytetrafluoroethylene (PTFE)coated fabric assembly was higher than those of the polyester polymer-coated fabric assembly and rubbercoated fabric assembly. Shabaridharan and Das 37 measured the thermal and water vapor resistance of nine through air-bonded nonwoven fabrics plus the inner and outer layer and found significant effects of mass per unit area of the middle layer on the thermal and water vapor resistance of through air-bonded nonwoven fabrics. In addition, the significant effects of the pore size of the outer layer on the water vapor resistance of air-bonded nonwoven fabrics were observed.…”
Section: Effects Of Raw Materials On Heat and Water Vapor Transfer Through Multilayer Fabricsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, they analyzed the effect of pore size and porosity on thermal and evaporative resistances of coated fabrics. It was found that the mass per unit area of through air-bonded nonwoven and pore size of coated fabric were found to have significant effect on thermal and evaporative resistances of multilayered fabric ensembles [13].…”
Section: Optimization Of Coating Parameters For Air Permeability Of Dmentioning
confidence: 99%